2021
DOI: 10.3390/w13182575
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influencing Factors of Drought Events Based on GRACE Data under Different Climatic Conditions: A Case Study in Mainland China

Abstract: The occurrence of droughts has become more frequent, and their intensity has increased in mainland China. With the aim of better understanding the influence of climate background on drought events in this region, we analyzed the role of the drought-related factors and extreme climate in the formation of droughts by investigating the relationship between the drought severity index (denoted as GRACE-DSI) based on the terrestrial water storage changes (TWSCs) derived from Gravity Recovery and Climate Experiment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…This may be related to the main stream of the Mekong River flowing through this region. The annual runoff of this river ranks ninth in the world, and runoff is an important part of TWSC [40]. From Figure 8d, we found that, similar to TWSC, PPT and ET, only regions NW and S have significant change trends in burned areas.…”
Section: Long-term Trend Changementioning
confidence: 79%
See 3 more Smart Citations
“…This may be related to the main stream of the Mekong River flowing through this region. The annual runoff of this river ranks ninth in the world, and runoff is an important part of TWSC [40]. From Figure 8d, we found that, similar to TWSC, PPT and ET, only regions NW and S have significant change trends in burned areas.…”
Section: Long-term Trend Changementioning
confidence: 79%
“…The degree-1 coefficients have been replaced using the results from Swenson et al [39]. To minimize the effects of high-frequency and correlated errors, the combined filtering (300 km Fan filter and de-striping method P3M6) has been applied for smoothing the SH solutions [40]. To reduce the signal attenuation effect caused by order truncation and filter smoothing, the GRACE TWSC data was corrected by using the scale factor approach [41].…”
Section: Grace Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the global warming trend has intensified, leading to frequent extreme disasters (flood and drought) around the world. Previous studies [8][9][10] indicate the precipitation (PPT) and evapotranspiration (ET) are the main driving factors of the regional water cycle as well as the important factors leading to regional TWSC. Anyah et al [11] analyzed the relationship between TWSC in Africa and five climate indices during the period 2003-2012, and the results show that there is a significant correlation between the above natural indices and TWSC.…”
Section: Introductionmentioning
confidence: 99%